Male and Female Conceptualizations of Sexual Harassment in Tanzania: The Role of Consent, Male Power, and Social Norms. Issue 19 (October 2022) - Wamoyi, Joyce; Ranganathan, Meghna; Mugunga, Samuel; Stöckl, Heidi
Sexual harassment is pervasive worldwide, yet there is a lack of clarity on its conceptualization in many settings, especially in low-income countries. Context-specific conceptualization of sexual harassment is vital to develop effective measurement tools, estimate its magnitude, and the design of interventions to address it. We explored how different population groups in Mwanza, Tanzania, understood, conceptualized, and experienced sexual harassment. This study employed a qualitative research design involving 74 in-depth interviews and 13 focus group discussions with participants from educational, workplace, and public settings in Mwanza, Tanzania. Participants were adolescent girls and boys, adult women and men. We explored individual-level perceptions and experiences of sexual harassment, and community norms and expectations around sexual harassment. We analyzed the data using a thematic approach. Participants' perceptions of sexual harassment emphasized the critical role of consent, the expression of male power, and social norms with regard to sexual harassment. Sexual harassment was understood to be a result of men being in positions of power and in charge of material resources, school grades, or employment opportunities. These in turn enabled them to take advantage of girls and women. Social norms around male and female interactions, courtship and seduction, expressions of sexual interest were crucial in delineating what was and what was not considered sexual harassment. Sexual harassment is a fluid concept, and its definition is highly dependent on contextual factors. Consent underpins the conceptualization of sexual harassment and is a fundamental feature in the definition and measurement of sexual harassment in Tanzania. Consent is largely determined by sexual norms around male and female interactions and gendered power. There is a need for consensus in schools, workplaces, and communities about what constitutes sexual harassment in order to measure and address it appropriately.